TRACES OF THE TRANSFORMATION OF ISLAMIC LAW; A HISTORICAL STUDY FROM THE INDEPENDENCE ERA TO THE REFORM ERA - Zuriah Zuriah; Asasriwarni; Ikhwan (Jurnal Ikhtibar Nusantara, 2026)
The transformation of Islamic law in Indonesia is a dynamic process that is inextricably linked to historical, political and social developments from the era of independence to the Reformation. This study aims to describe how Islamic law has undergone changes and integration into the pluralistic national legal system. The method used is a qualitative approach with a descriptive research design based on a literature review of various academic sources. The findings indicate that in the early years of independence, Islamic law had not yet been formally institutionalised, but was already practised as a social norm within society. During the New Order era, a process of institutionalisation took place through legislation such as the 1974 Marriage Law, the Compilation of Islamic Law (KHI), and the strengthening of the Religious Courts. Meanwhile, the Reform era became a crucial phase marked by an increasing openness to the expression of Islamic law, both through national legislation and regional regulations based on sharia. This transformation demonstrates that Islamic law functions not only as a religious norm but also as a source of values in the formation of national law. However, this process faces various challenges, such as legal pluralism, differences in fiqh interpretations, the demands of modernity and globalisation, and the potential for the politicisation of Islamic law. Furthermore, the issue of the formalisation of Islamic criminal law remains a subject of debate with no consensus yet reached. Therefore, an inclusive, adaptive, and contextual approach is required in integrating Islamic law into the national legal system. Thus, the transformation of Islamic law in Indonesia reflects ongoing efforts to harmonise Islamic values with the principles of a modern rule of law that upholds justice and the public interest.